Control design of forward-reverse induction motor - Adilah, Mansor (Universiti Malaysia Perlis, 2009)
Induction motor is the most important part that makes this project success. This motor is chosen because it simple, rugged construction, easy maintenance and cost effective pricing. It’s commonly used especially for higher-powered motors. For this project, Induction Motor has to running in forward-reverse controlled by limit switch. These limit switch use as a sensor that detect the thing or object when it touched. The motor will stop at the moment before it continue running in reverse direction. This application is same as conveyor that use in workhorses industry. The main part of this project is to measure the time that induction motor take when it need to change forward direction to reverse direction. From investigation the time is influenced by the speed of motor. When the speed of induction motor is high, the time to change direction is longest.